PELAYARAN RAKYAT DALAM PERSPEKTIF SISTEM LOGISTIK NASIONAL - Yusuf Romadhon; Resista Vikaliana Vikaliana (Jurnal Logistik Indonesia, 2017)
The State of Indonesia is a country which is according to cultural history and in the days of the kingdom is a maritime country. The country of Indonesia with the largest  islands covers the largest sea, the largest island, and the second longest beach in the world. On this basis, Indonesia currently has a modern port as well as a port for people's voyages. People's voyages are generally identical to traditional wooden boats operated by natural sailors with simple management (Law No. 17/2008 on the voyage of articles 15, paragraphs 1 and 2). The demands of global business are causing people's shipping today to be marginalized.Some problems in the voyage of the people include the procurement of the shipping fleet is hampered by the difficult supply of logs, so it needs to look for other alternatives. Another problem is the guarantee of safety and good service from the voyage of the people The government plans to build the People's Port. This port will be built with a good security system. The sailing of people with the zone of its own. People's voyages are still needed, because remote areas that are not crossed by large auto ships are still dependent on small ships such as KLM  or PLM. In addition, there is a dock that can not be enclosed by iron vessels or shallow harbors. The voyage of the people can overcome it, thus helping national transpotation.Indonesia as the largest archipelago country still requires the voyage of the people as one mode of inter island transportation. The Government is committed to memordenisasi and improve the safety and security of people's shipping by still considering local wisdom. Another problem is the guarantee of safety and good service from the voyage of the people.